PENGARUH INTENSITAS PENGGUNAAN SMARTPHONE DAN SUMBER BELAJAR TERHADAP KEMAMPUAN KOGNITIF SISWA SMKS KRISTEN 2 TOMOHON - Kuhu, Fanly; Kambey, Joseph; Kandori, Iwan; Wokas, Starry (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2024)
This research aims to determine the partial and simultaneous influence of the intensity of smartphone use and learning resources on the cognitive abilities of FASE E Class X and XI in SMKS Kristen 2 Tomohon students. This research method uses quantitative methods with multiple regression analysis with a total of 51 respondents, class X and XI FASE E students. The research results show that the t value for the intensity of Smartphone use is greater than the t table (3.675 > 1.677) while the t value for Learning Resources is also greater than the t table (2.034 > 1.677) where it can be concluded that there is a partially significant influence on the intensity of Smartphone use and learning resources on students' cognitive abilities, the simultaneous influence can be seen from the calculated f value where the calculated f is greater than f table (8.618> 3.19) meaning that there is a significant simultaneous influence on the intensity of smartphone use and learning resources on FASE students' cognitive abilities E Class X and XI at Christian Vocational School 2 Tomohon.